Conventional chemotherapy (CHOEP-14) with rituximab or high-dose chemotherapy (MegaCHOEP) with rituximab for young, high-risk patients with aggressive B-cell lymphoma: an open-label, randomised, phase 3 trial (DSHNHL 2002-1). - Schmitz, N.; Nickelsen, M.; Ziepert, M.; Haenel, M.; Borchmann, P.; Schmidt, C.; Viardot, A.; Bentz, M.; Peter, N.; Ehninger, G.; Doelken, G.; Ruebe, C.; et al. (Lancet Oncol, 2012)
BACKGROUND: High-dose therapy (HDT) followed by transplantation of autologous haemopoietic stem cells is frequently done as part of first-line therapy in young patients with high-risk aggressive B-cell lymphoma. We investigated whether HDT with cytotoxic agents identical to those used for conventional therapy followed by autologous stem-cell transplantation (ASCT) improved survival outcome compared with conventional chemotherapy when rituximab was added to both modalities. METHODS: We did an open-label, randomised trial comparing conventional chemotherapy (cyclophosphamide, doxorubicin, vincristine, etoposide, prednisone) and rituximab (R-CHOEP-14) with dose-escalated sequential HDT and rituximab (R-MegaCHOEP) followed by repetitive ASCT in high-risk (age-adjusted International Prognostic Index [IPI] 2 or 3) patients aged 18-60 years with aggressive B-cell lymphoma. Eligible patients received radiotherapy for bulky, extranodal disease, or both. Randomisation (1:1) used the Pocock minimisation algorithm; patients were stratified by age-adjusted IPI factors, bulky disease, and centre. The primary endpoint was event-free survival. All analyses were done on the intention-to-treat population. This trial is registered with ClinicalTrials.gov, number NCT00129090. FINDINGS: 136 patients were randomly assigned to R-CHOEP-14 and 139 to R-MegaCHOEP. 130 patients in the R-CHOEP-14 group and 132 in the R-MegaCHOEP group were included in the intention-to-treat population. After a median of 42 months (IQR 29-59), 3-year event-free survival was 69.5% (95% CI 61.3-77.7) in the R-CHOEP-14 group and 61.4% (52.8-70.0) in the R-MegaCHOEP group (p=0.14; hazard ratio 1.3, 95% CI 0.9-2.0). All 128 evaluable patients treated with R-MegaCHOEP had grade 4 leucopenia, as did 48 (58.5%) of 82 patients with documented blood counts in the R-CHOEP-14 group. All 128 evaluable patients in the R-MegaCHOEP group had grade 3-4 thrombocytopenia, as did 26 (33.8%) of 77 patients in the R-CHOEP-14 group with documented blood counts. The most important non-haematological grade 3 or 4 adverse event was infection, which occurred in 96 (75.0%) of 128 patients treated with R-MegaCHOEP and in 40 (31.3%) of 128 patients treated with R-CHOEP-14. INTERPRETATION: In young patients with high-risk aggressive B-cell lymphoma, R-MegaCHOEP was not superior to conventional R-CHOEP therapy and was associated with significantly more toxic effects. R-CHOEP-14 with or without radiotherapy remains a treatment option for these patients, with encouraging efficacy. FUNDING: Deutsche Krebshilfe.
Keywords: Adolescent; Adult; Antibodies, Monoclonal, Murine-Derived/*administration & dosage; Antineoplastic Combined Chemotherapy Protocols/administration & dosage/*therapeutic use; Cyclophosphamide/administration & dosage; Doxorubicin/administration & dosage; Etoposide/administration & dosage; Female; Humans; Lymphoma, B-Cell/*drug therapy; Male; Middle Aged; Prednisolone/administration & dosage; Rituximab; Vincristine/administration & dosage; Young Adult